If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(2x+5)=3(x-6)
We move all terms to the left:
2(2x+5)-(3(x-6))=0
We multiply parentheses
4x-(3(x-6))+10=0
We calculate terms in parentheses: -(3(x-6)), so:We get rid of parentheses
3(x-6)
We multiply parentheses
3x-18
Back to the equation:
-(3x-18)
4x-3x+18+10=0
We add all the numbers together, and all the variables
x+28=0
We move all terms containing x to the left, all other terms to the right
x=-28
| 11+7.1n=9+7.5n | | (−3)5x=−1875 | | 8(-r-8)=-88 | | X+1/3x+5=17 | | 2y-4+3(y+1)=-31 | | 2(2x+5)=3(x-6 | | 6c+15=75 | | 4(m-12)=10m-6m(m-8) | | w+w-44+w-33=180 | | 3(x−6)+6=5x−2 | | 7n-n=-6 | | 100(z-0.2)=-10(52+0.8) | | 1/3(x+5)=17 | | 5y-6-3y=4 | | 2b+5=3 | | 6x+12=-2x+36 | | 1/n-3=1/4 | | 5.x+3=8 | | 8(x+2)=8(x-4) | | X^2+16x-237=0 | | n*9=18 | | 6x=1-8 | | x^2+10x+21=(x+3)() | | 2b+5b=0 | | x/5x=20 | | 8c+10=0 | | n9=18 | | 6=1-8x | | 9(x+9)=-45 | | x+(-15)=-12 | | v+v-6=v+39 | | -2/3x-1/12=8 |